2020
DOI: 10.1097/wnp.0000000000000609
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Normal Values for F-Wave Latencies in Diagnosing Peripheral Neuropathies for the Pediatric Population

Abstract: Purpose: We present a unique technique applying F-wave latencies to assist in the diagnosis of peripheral neuropathy within the pediatric age group. Methods: We calculated an F-wave estimated deviance adjusted for limb length measurements, distal motor conduction velocity, and distal motor latencies. We compared the F-wave estimated deviance from the normal subjects with those with peripheral neuropathy (both axonal and demyelinating) to establish diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Eight articles pertaining to normal pediatric F response latencies were found from the past 35 years (Table ). Five of the studies also provided data pertaining to sensory and motor nerve conductions studies as noted above, whereas three studies focused specifically on F‐wave data for children <18 years old . Six studies provided infant data, of which five reported a progressive decrease in minimum F‐response latency from the neonatal period (< 28 days), early infancy (1‐6 months), older infancy (7‐12 months), to the toddler years (1‐3 years) .…”
Section: Resultsmentioning
confidence: 99%
“…Eight articles pertaining to normal pediatric F response latencies were found from the past 35 years (Table ). Five of the studies also provided data pertaining to sensory and motor nerve conductions studies as noted above, whereas three studies focused specifically on F‐wave data for children <18 years old . Six studies provided infant data, of which five reported a progressive decrease in minimum F‐response latency from the neonatal period (< 28 days), early infancy (1‐6 months), older infancy (7‐12 months), to the toddler years (1‐3 years) .…”
Section: Resultsmentioning
confidence: 99%